AN INNOVATIVE METHOD OF TEACHER SELF-DEVELOPMENT IN PEDAGOGICAL ACTIVITY - Musayeva , Muhabbat (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
The article analyzes the theoretical foundations, modern methodologies, and practical mechanisms of a teacher’s self-development process in pedagogical activity. In the context of an expanding digital learning environment, the use of artificial intelligence tools, and increasing demands for continuous professional growth, new paradigms of teacher self-development are examined. Based on the current state of the education system of Uzbekistan and the requirements within the framework of the “Digital Uzbekistan — 2030” strategy, a proposed practical model and its stages are presented.